Uncovering the Philippines and Indonesian Teachers' Pedagogical Beliefs in the 21st Century Learning - Herda, Rozanah; Lampito, Octo; Travero, Arnel (LPPM Universitas Advent Indonesia, 2025)
English as the medium of teaching in this 21-st century learning demands teachers to be more competent and professional. In the EFL context, the English-integrated skills should be mastered by professional teachers to teach and design learning scenarios based on the skill. However, multifaceted issues and challenges are faced by teachers. This quantitative study with a causal-comparative design aimed at revealing the Philippines and Indonesian Teachers' Pedagogical Beliefs in Teaching English. This study had two research questions: 1). How are The Philippines and Indonesian teachers' pedagogical beliefs on teaching English? and 2) Are there any different findings on pedagogical beliefs between The Philippines and Indonesian teachers'? This study involved 30 EFL teachers from the Philippines (N=15) and Indonesia (N=15). The participants were selected randomly from state and vocational institutions in the Philippines and Indonesia. The data were collected through a close-ended questionnaire, and the descriptive statistic was analyzed using SPSS version 25. The findings revealed that teachers in both countries showed a good pedagogical perspective. However, a finding from the Philippines group showed teachers chose to be neutral in giving additional learning material and media to students. These findings gave the researchers broader input on how teachers in the Philippines and Indonesia showed their professional perspectives on teaching aspects. Keywords: Teachers' Beliefs, Pedagogy, Teaching English